High-fidelity haptic and visual rendering for patient-specific simulation of temporal bone surgery. Issue 1 (1st January 2016) - Chan, Sonny; Li, Peter; Locketz, Garrett; Salisbury, Kenneth; Blevins, Nikolas H.
Abstract: Medical imaging techniques provide a wealth of information for surgical preparation, but it is still often the case that surgeons are examining three-dimensional pre-operative image data as a series of two-dimensional images. With recent advances in visual computing and interactive technologies, there is much opportunity to provide surgeons an ability to actively manipulate and interpret digital image data in a surgically meaningful way. This article describes the design and initial evaluation of a virtual surgical environment that supports patient-specific simulation of temporal bone surgery using pre-operative medical image data. Computational methods are presented that enable six degree-of-freedom haptic feedback during manipulation, and that simulate virtual dissection according to the mechanical principles of orthogonal cutting and abrasive wear. A highly efficient direct volume renderer simultaneously provides high-fidelity visual feedback during surgical manipulation of the virtual anatomy. The resulting virtual surgical environment was assessed by evaluating its ability to replicate findings in the operating room, using pre-operative imaging of the same patient. Correspondences between surgical exposure, anatomical features, and the locations of pathology were readily observed when comparing intra-operative video with the simulation, indicating the predictive ability of the virtual surgical environment.